2011
DOI: 10.1371/journal.pone.0026507
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterisation of an Iron-Responsive Candidate Probiotic

Abstract: BackgroundIron is an essential cofactor in almost all biological systems. The lactic acid bacteria (LAB), frequently employed as probiotics, are unusual in having little or no requirement for iron. Iron in the human body is sequestered by transferrins and lactoferrin, limiting bacterial growth. An increase in the availability of iron in the intestine by bleeding, surgery, or under stress leads to an increase in the growth and virulence of many pathogens. Under these high iron conditions, LAB are rapidly out-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Additionally, increased leaks which occur as a result of epithelial cell apoptosis have been observed in Crohn's disease and ulcerative colitis (Heller et al, 2005;Zeissig et al, 2007). We have previously shown that S. thermophilus prevents occludin degradation and breakdown of tight cell junctions induced by E. coli in vitro as well as reducing epithelial cell death (Bailey et al, 2011). In the data presented here, we have shown that S. thermophilus prevents bacterial translocation from the lumen of the gut into the intestinal tissue in colitic animals ( Figure 4).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Additionally, increased leaks which occur as a result of epithelial cell apoptosis have been observed in Crohn's disease and ulcerative colitis (Heller et al, 2005;Zeissig et al, 2007). We have previously shown that S. thermophilus prevents occludin degradation and breakdown of tight cell junctions induced by E. coli in vitro as well as reducing epithelial cell death (Bailey et al, 2011). In the data presented here, we have shown that S. thermophilus prevents bacterial translocation from the lumen of the gut into the intestinal tissue in colitic animals ( Figure 4).…”
Section: Discussionmentioning
confidence: 95%
“…Competition both for limited nutrients and physical attachment sites could assist in the elimination of pathogens and opportunistic pathogens. We have previously shown that, unlike the majority of conventional probiotics, S. thermophilus NCIMB 41856 can compete with the resident microflora for iron, abundant in the IBD gut and used by many bacterial strains as a growth factor (Bailey et al, 2011). In the data presented here, we have shown that, in addition to this, it can compete for physical attachment sites at the iron-rich intestinal mucosa and therefore occupy a niche which could otherwise be inhabited by potentially pathogenic bacterial species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations